Project, toolkit, and database of neuroinformatics ecosystem: A summary of previous studies on “Frontiers in Neuroinformatics” - Li, Xin; Liang, Huadong (Frontiers in Neuroinformatics, 2022)
In the field of neuroscience, the core of cohort study project consists in the collection, analysis and sharing of multi-modal data. Recent years has witnessed a host of efficient and high-quality toolkits published and employed to improve the quality of multi-modal data in cohort study. In turn, to glean answers to relevant questions from such a huge collection of papers is a time-consuming task for cohort researchers. As part of our efforts to tackle this problem, we propose a hierarchical neuroscience knowledge base that consists of projects/organizations, multi-modal databases and toolkits, so as to facilitate researchers’ answer searching process. We first classified the topics of the articles in Frontiers in Neuroinformatics according to the multi-modal data life cycle, and from these articles extracted such information objects as projects/organizations, multi-modal databases, and toolkits. Then, we map these information objects into our proposed knowledge base framework. A Python-based query tool has also been developed in tandem for quicker access the knowledge base, (accessible at https://github.com/Romantic-Pumpkin/PDT_fninf). Finally, based on constructed knowledge base, we discussed some key research issues and underlying trends in different stages of the multi-modal data life cycle.